PENGONTROLAN LAMPU DENGAN ANDROID BERBASIS MIKROKONTROLER VIA HOTSPOT MENGGUNAKAN VOICE RECOGNITION - Yusran Yusran; Dwi Winarti; Ellbert Hutabri; Koko Handoko (Politeknik Bisnis Indonesia, 2023)
Smart living is a living concept that is based on practicality and efficiency but still upholds comfort. In line with the high mobility of big city people who have a fast-paced and practical lifestyle, smart living is the solution, especially by utilizing technology in housing. One of the uses of residential technology is controlling lights using hardware and designing software using the Arduino IDE so that later the lights can be controlled using a smartphone owned by the user using voice recognition. Voice recognition is the concept of controlling electronic equipment using the user's voice. The application of this control system becomes more efficient in saving time and effort because you don't have to walk to every room to turn off or turn on the lighting, users can use the Google Assistant application on an Android-based smartphone with the turn on the light one command. The results of the designed tool are able to provide practicality and efficiency for its users because it can control the lights remotely.